PENGEMBANGAN MEDIA PEMBELAJARAN POSTER DIGITAL PADA MATERI IPS KELAS VI UNTUK MENINGKATKAN KUALITAS BELAJAR MENGAJAR - Sadiyah, Faiqhotus; Rezania, Vanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research was conducted because of the importance of teaching materials as a support for the teaching and learning process, namely by using digital poster media. Digital poster media, namely electronic poster teaching materials with graphic designs that can communicate visual messages or information in a form that is not easily damaged and used by students during the learning process. This digital poster media can help teachers to improve their teaching skills through the use of interesting media by utilizing current technological developments, so that learning becomes more interactive, creative and fun for students. The purpose of this study was to produce digital learning media in the form of posters and to find out the feasibility of digital poster-based learning media in the learning process, which was seen from student responses, implementation, and effectiveness of the digital poster media. The research method used is research and development with the ADDIE model. The product developed is in the form of digital poster learning media on social studies material for class VI theme 9. Data collection techniques use interview sheets for class VI teachers, material and media expert validation for UMSIDA lecturers, effectiveness sheets for class VI teachers, digital poster media implementation sheets, sheets test of learning outcomes after using digital poster media, and questionnaires on student responses to digital poster media. The validation results of media experts are 84%, material experts are 94%. The results of student responses to digital poster media were very feasible with a score. The results of implementing the benefits of digital poster media obtained results of 88% in the feasible category. The results of the effectiveness data obtained results of 88% in the category of very effective and suitable for use in learning. As well as student learning outcomes increased with the acquisition of an average score of 92 above the KKM score.